2011
DOI: 10.2514/1.c000205
|View full text |Cite
|
Sign up to set email alerts
|

Sizing of a Fully Integrated Hypersonic Commercial Airliner

Abstract: A study was conducted to demonstrate an approach to sizing of a fully integrated hypersonic commercial airliner, which was based on the parametric sizing methodology. It consisted of defining a set of equations that relates mission requirements to geometry, aerodynamic, and propulsion efficiencies, which were solved simultaneously. The next step involved identifying the final configuration of a wholly integrated hypersonic vehicle with trimming, control surfaces, and an integrated propulsion system. Vehicle we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Of the three fuels that meet the high thrust requirement, beryllium offers the best yield. However, since the data available on beryllium are scarce, and there are no experimental data on the temperature auto ignition [3], that option was discarded, while recognizing its validity when more accurate data are available. Ideal performance of Aluminum and Magnesium reacting with CO2 in a rocket chamber have been calculated at 70 km altitude, and assuming the combustor inlet conditions at M = 8 flight speed, (i.e.…”
Section: Investigation Of Fuels For the Venusian Atmospherementioning
confidence: 98%
See 1 more Smart Citation
“…Of the three fuels that meet the high thrust requirement, beryllium offers the best yield. However, since the data available on beryllium are scarce, and there are no experimental data on the temperature auto ignition [3], that option was discarded, while recognizing its validity when more accurate data are available. Ideal performance of Aluminum and Magnesium reacting with CO2 in a rocket chamber have been calculated at 70 km altitude, and assuming the combustor inlet conditions at M = 8 flight speed, (i.e.…”
Section: Investigation Of Fuels For the Venusian Atmospherementioning
confidence: 98%
“…Recent studies [3] have shown that fuels that provide the best performance when reacting with the CO2-rich atmosphere of Mars/Venus are light metals such as beryllium, magnesium and aluminum. This is because of the high specific impulse potentially available is at the highest possible O/F ratio, therefore maximizing also thrust.…”
Section: Investigation Of Fuels For the Venusian Atmospherementioning
confidence: 99%
“…The L/D ratio is the most important parameter driving hypersonic flight range. Generally speaking, as speed increases past M = 1, the aerodynamic lift coefficient CL diminishes while drag increases and, past M ~ 3, L/D drops rapidly: Figure 1 shows aerodynamic test data for the maximum L/D (as a function of the angle of attack) starting at M = 3, together with two theoretical curves developed by Küchemann [3][4][5] in the 1970s. Both are partially satisfactory, in the sense that the theoretical curves fit only parts of the data, and the data themselves are scattered.…”
Section: Cruisersmentioning
confidence: 99%
“…6 Furthermore, in other cases, multidimensional or parametric analyses have been included to assess the reliability of the solutions. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, in other cases, multidimensional or parametric analyses have been included to assess the reliability of the solutions. 7,8 In this context, this paper aims at further extending the current version of the MC methodology and tool to specifically manage the design of high-speed vehicles, providing updated and/or brand-new mathematical formulations to cope with the supersonic and hypersonic mission phases. The development of such a powerful tool, based on a rigorous methodology, will provide engineers with a valuable support to address the worldwide incentive to consider commercial high-speed transportation systems for both aeronautical and space applications.…”
Section: Introductionmentioning
confidence: 99%